SYNTHESIS AND BIOLOGICAL EVALUATION OF NICOTINIC ACID PEPTIDE DERIVATIVES - Dhir, Nisha; Kaur, Gagan Preet (Journal of Biomedical and Pharmaceutical Research, 2019)
The present study deals with the synthesis of nicotinic acid peptide derivatives and comparative evaluation of biological activities, such as antibacterial and antifungal. Among hetrocyclic aromatic compounds, pyridine nucleus is found in many bioactive products and incorporation of amino acids and peptides into the hetrocyclic aromatic congeners have resulted in compounds with potent activities. All the compounds were synthesized by coupling of nicotinic acids with amino acid methyl esters/dipeptides/tripeptides/tetrapeptides in presence of DCC as coupling agent and NMM as base under continuous stirring for 36 hrs. All synthesized peptide derivatives were identified on the basis of melting point range, Rf values, solubility studies, IR and 1H NMR spectral data. The antimicrobial activity of synthesized compounds was determined against bacterial strainsviz. E. Coli and S. Aureus and fungal strains viz. C. albicans and A. Niger using ciprofloxacin and fluconazole as standard respectively. All the synthesized compounds showed good to moderate antimicrobial activity at 40, 80 and 160 μg/ml. The comparative studies showed the following order of activity profile: nicotinic acid <nicotinic acid methylesters>dipeptide >tripeptide>tetrapeptide. Keywords: Nicotinic acid, Peptides, Antimicrobial activity.